Thin film thinning and surface treatment method, low-roughness YIG thin film and application
By combining sandpaper grinding, polishing cloth polishing and argon ion etching technology, the YIG film is thinned and surface treated, which solves the stress and roughness problems of single-crystal YIG ferrite thick film during the preparation process, and realizes the High-efficiency, low-roughness film preparation, suitable for microwave devices applications.
Patent Information
- Application Number
- CN202411369284.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-02-11
AI Technical Summary
The prior art has large residual stress and high surface roughness when preparing single crystal YIG ferrite thick films, which affects the performance of magnetic functional substrates. Especially when used in microwave devices, it is difficult to meet miniaturization and low power consumption. and high integration requirements.
Thickness thinning and surface treatment methods are adopted, including using sandpaper for main thinning, followed by W1.5~W2.5 polishing cloth for thinning and polishing, and finally further thinning and improving surface roughness through argon ion etching and polishing technology. .
The high thinning rate, low surface roughness and accurate target thickness of YIG films are achieved, meeting the needs of low stress and high precision surface treatment in microwave devices.
Smart Images

Figure CN119407678A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of YIG film preparation, and in particular to a film thinning and surface treatment method, a YIG film with low surface roughness and applications. Background Art
[0002] Ferrite materials excel in broadband frequency tuning at microwave and millimeter wave frequencies. Among them, YIG ferrites are widely used in gyromagnetic single crystal devices in the microwave frequency band, such as oscillators, filters, frequency multipliers, etc. In addition, phase shifters using ferrite materials have shown large phase shifts, low insertion losses, and high power handling capabilities. 3 Fe 5 O 12 ) is a member of the ferrite family of materials that has these excellent qualities and is very suitable for phase shifter design. It is also commonly used as a magnetic material to control the magnetic permeability of propagating microwave signals.
[0003] Single crystal YIG ferrite thick film has large residual stress during the preparation process. When the thick film is subsequently used as a magnetic functional substrate, the surface roughness of the single crystal YIG ferrite thick film increases with the increase of the film thickness. When the roughness reaches the order of hundreds of nanometers or more, it will seriously affect the functional realization of the metal graphic circuit on the single crystal YIG ferrite thick film substrate. Therefore, it is necessary to perform low-stress fine polishing on the surface of the single crystal YIG ferrite thick film to meet the requirements of coating and micro-machining. The research on YIG thin films in China started late, and there are obvious differences in the YIG thick film processing technology with foreign countries, which has led to the slow development of miniaturized microwave ferrite devices and severely restricted the development of my country in the field of high-performance active phased array radar. In order to meet the requirements of phased array radar for small size, low power consumption, high integration and other performance of phase shifters, the research on single crystal YIG thick film devices is of great significance to the development of phased array radar. Summary of the invention
[0004] The purpose of the present invention is to solve at least one of the above-mentioned deficiencies in the prior art. For example, one of the purposes of the present invention is to provide a method for thinning and surface treatment of a thin film; a second purpose of the present invention is to provide a YIG thin film with low surface roughness; a third purpose of the present invention is to provide an application of the YIG thin film in a microwave device.
[0005] In order to achieve the above objectives, the present invention provides a method for thinning and surface treating a YIG film.
[0006] The method may include: using sandpaper to mainly thin the YIG film; using W1.5-W2.5 polishing cloth to thin and polish the YIG film treated with sandpaper to remove surface scratches and improve roughness; using argon ion etching polishing technology to thin and polish the YIG film treated with the polishing cloth.
[0007] Optionally, the mesh number of the sandpaper is ≥7000 mesh and ≤10000 mesh.
[0008] Optionally, the main thinning is performed based on a grinder, wherein the grinder speed is 60-70 r / min, the grinding liquid includes water, the grinding liquid drop acceleration rate is 20-30 mL / min, the applied pressure is 0.2-0.25 MPa, and the grinding time is 3 min ± 10 s.
[0009] Optionally, the polishing cloth thins and polishes the YIG film treated with sandpaper based on a grinder, wherein the grinder speed is 60-70 r / min, the grinding liquid is an aluminum oxide polishing liquid with a particle size of 0.5-2 μm, the grinding liquid droplet acceleration rate is 20-30 mL / min, the applied pressure is 0.2-0.25 MPa, and the polishing time is 10 min ± 10 s.
[0010] Alternatively, the polishing cloth may include a red velvet polishing cloth.
[0011] Optionally, the method further includes cleaning the YIG film after being treated with the polishing cloth before using the argon ion etching polishing technology.
[0012] Wherein, acetone is used for the cleaning.
[0013] Optionally, the process parameters of the argon ion etching polishing technology include: gas flow rate of 7-10 sccm, argon ion beam incident angle of 80-90°, argon ion energy range of 100-1000 eV, ion beam current density of 0-1 mA / cm 2 , beam current 0 ~ 130mA, effective ion beam diameter ≥ 100mm, single etching time is 10 ~ 600s.
[0014] Another aspect of the present invention provides a YIG film with low surface roughness.
[0015] The YIG film is prepared by the above method. The roughness of the YIG film with low surface roughness is ≤2nm and the thickness is 1-50μm.
[0016] Another aspect of the present invention provides application of the YIG film in microwave devices.
[0017] Compared with the prior art, the beneficial effects of the present invention include at least one of the following:
[0018] (1) The YIG film thickness reduction and surface treatment method of the present invention combines mechanical grinding and polishing with argon ion etching, so that the prepared YIG film has the advantages of high thinning rate, low surface roughness and relatively accurate target thickness.
[0019] (2) The samples prepared by the present invention not only meet the specific thickness requirements, but also have excellent surface roughness.
[0020] (3) The YIG thin film prepared by the present invention has a simple process, high operability, and can be widely used.
[0021] (4) The YIG film prepared by the present invention can be used in microwave devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 A scanning electron microscope (SEM) image of the YIG thin film obtained in Example 1 of the present invention is shown;
[0023] Figure 2 The surface atomic force microscope (AFM) image of the YIG thin film obtained in Example 1 of the present invention is shown;
[0024] Figure 3 The SEM image of the YIG film obtained in Comparative Example 1 of the present invention is shown;
[0025] Figure 4 An AFM image of the YIG thin film obtained in Comparative Example 1 of the present invention is shown;
[0026] Figure 5 The SEM image of the YIG film obtained in Comparative Example 2 of the present invention is shown;
[0027] Figure 6 The AFM image of the YIG thin film obtained in Comparative Example 2 of the present invention is shown. DETAILED DESCRIPTION
[0028] Hereinafter, the thin film thinning and surface treatment method, the low-roughness YIG film and the application of the present invention will be described in detail in conjunction with exemplary embodiments.
[0029] Exemplary Embodiment 1
[0030] This exemplary embodiment provides a method for reducing the thickness of a YIG thin film and performing surface treatment.
[0031] The preparation method may include the following steps:
[0032] S1. Use sandpaper to perform major thinning of the YIG film.
[0033] In this embodiment, the mesh number of the sandpaper is ≥7000 mesh and ≤10000 mesh. The lower the mesh number of the sandpaper, the coarser the grinding particles and the greater the thinning rate. The advantage of using sandpaper with a mesh number ≥7000 mesh is that it is not easy to have excessive thinning. For example, when using 5000 mesh sandpaper to grind the surface of the YIG film, there are large surface scratches. The higher the mesh number of the sandpaper, the finer the grinding particles, and the smaller the scratches produced during the grinding contact. However, if the mesh number is too high, the thinning effect of the sandpaper will weaken, the thinning rate will decrease, and the polishing effect will become stronger. Therefore, in this embodiment, the mesh number of the sandpaper is ≥7000 mesh and ≤10000 mesh, such as 7500 mesh, 8000 mesh, 9000 mesh, etc.
[0034] In this embodiment, the main thinning is performed based on a grinder. The grinding machine speed is 60-70r / min, such as 61, 65, 69r / min, etc. The grinding liquid may include water, and the grinding liquid droplet acceleration rate is 20-30mL / min, such as 21, 25, 29mL / min, etc. The applied pressure is 0.2-0.25MPa, such as 0.21, 0.23, 0.24MPa, etc. The grinding time is 3min±10s, such as 2min 55s, 3min05s, 3mim 09s, etc.
[0035] S2. Use a polishing cloth with a particle size of W1.5 to W2.5 to thin and polish the YIG film treated with sandpaper to remove surface scratches and improve roughness.
[0036] In this embodiment, the thinning and polishing are carried out based on a grinder, wherein the grinder speed is 60-70 r / min, the grinding liquid is an aluminum oxide polishing liquid with a particle size of 0.5-2 μm, the grinding liquid droplet acceleration rate is 20-30 mL / min, the applied pressure is 0.2-0.25 MPa, and the polishing time is 10 min ± 10 s, for example 9 min 55 s, 10 min 05 s, 10 min 09 s.
[0037] In this embodiment, the polishing cloth comprises a red velvet polishing cloth.
[0038] The purpose of polishing is to remove surface scratches and improve roughness. The smaller the particle size of the polishing cloth, the finer the abrasive particles, the lower the thinning rate, and the better the polishing effect. In this embodiment, the suitable range of the particle size of the polishing cloth is W1.5 to W2.5, such as W1.8, W2.0, W2.3, etc.
[0039] In this embodiment, the YIG film treated with the polishing cloth needs to be cleaned with acetone to remove the hot melt adhesive and other impurities and dirt.
[0040] S3. Use argon ion etching and polishing technology to thin and polish the YIG film treated with the polishing cloth.
[0041] In this embodiment, the process parameters of the argon ion etching technology are: gas flow rate is 7-10sccm, for example, 7, 7.5, 8, 9, 9.5sccm, etc.; argon ion beam incident angle is 80-90°, for example, 80, 83, 85, 89°; argon ion energy range is 100-1000eV, for example, 100, 110, 200, 500, 980eV, etc.; ion beam current density is 0-1mA / cm 2 , for example 0.1, 0.2, 0.5, 0.8, 0.9 mA / cm 2 etc.; beam current 0-130mA, for example 1, 2, 5, 10, 20, 50, 80, 100, 120, 129mA, etc.; effective ion beam diameter ≥100mm, for example 100, 120, 150, 200mm, etc.; single etching time is 10-600s, for example 10, 60, 100, 500, 580s, etc.
[0042] Among them, the purpose of using argon ion etching is to further thin and improve the surface roughness.
[0043] In order to better reflect the effect of the present invention, Tables 1 and 2 list the surface root mean square roughness comparison of the YIG film before and after being treated by different methods, and the thickness comparison of the YIG film before and after being treated by different methods.
[0044] Among them, the process corresponding to "YIG film sample 7000 mesh sandpaper 3 min treatment" in Table 1 and Table 2 specifically includes: based on a grinder, wherein the grinder speed is 70r / min, the grinding liquid includes water, the grinding liquid drop acceleration rate is 20mL / min, the applied pressure is 0.2MPa, and the grinding time is 3min.
[0045] The specific process corresponding to "polishing cloth for 10 minutes" includes: based on a grinder, wherein the grinder speed is 70r / min, the grinding liquid is an aluminum oxide polishing liquid with a particle size of 0.5μm, the grinding liquid droplet acceleration rate is 20mL / min, the applied pressure is 0.2MPa, and the polishing time is 10min; the polishing cloth is a red velvet polishing cloth with a particle size of W2.5.
[0046] The specific process corresponding to "argon ion etching for 1 hour" includes: the process parameters of the argon ion etching technology are: gas flow rate of 8sccm, argon ion beam incident angle of 90°, argon ion energy of 490eV, ion beam current density of 0.5mA / cm 2 , beam current 95mA, effective ion beam diameter 150mm, single etching time is 600s.
[0047] Table 1 Comparison of surface RMS roughness of YIG films before and after treatment by different methods
[0048]
[0049] As shown in Table 1, compared with the YIG film sample before treatment, the roughness of the YIG film sample in the embodiment becomes larger after mechanical thinning with 7000 mesh sandpaper for 3 minutes, and the surface roughness requirement of ≤2nm is not met, and scratches appear on some parts of the film surface. In the embodiment, after the YIG film is thinned with 7000 mesh sandpaper for 3 minutes, the roughness of the YIG film sample is reduced after further polishing with a finer polishing flannel for 10 minutes and argon ion etching for 1 hour. In the embodiment, the roughness of the YIG film sample is reduced the most after argon ion etching for 1 hour.
[0050] Table 2 Thickness comparison of YIG film before and after treatment by different methods
[0051]
[0052] As shown in Table 2, 7000-grit sandpaper can quickly thin the YIG film, but it does not meet the surface roughness requirement of ≤2nm, as shown in Table 1. Compared with mechanical thinning combined with sandpaper and polishing flannel + argon ion etching, the YIG film sample only subjected to argon ion etching meets the requirement of low surface roughness, but the thinning rate is significantly lower, and it takes longer and more costly to complete the thinning of the same thickness.
[0053] Exemplary Embodiment 2
[0054] The present exemplary embodiment provides a YIG thin film with low surface roughness.
[0055] The YIG film can be prepared by the method described in exemplary embodiment 1. The roughness of the YIG film with low surface roughness is ≤2nm, for example, 1.0, 1.5, 1.8, 1.9nm; the thickness is 1 to 50μm, for example, 1, 3, 4, 4.5, 5, 10, 20, 40, 49μm, etc.
[0056] Exemplary Embodiment 3
[0057] The present exemplary embodiment provides an application of a YIG thin film.
[0058] The applications may include applications in microwave devices.
[0059] In order to better understand the above exemplary embodiments, further description is given below with reference to specific examples.
[0060] Example 1
[0061] (1) Place a cylindrical iron column with a diameter of 20 mm, a height of 60 mm, and a weight of 180 g on a heating table. After heating, apply a certain amount of hot melt adhesive and place a 3 mm × 3 mm YIG film on it. Then remove it from the heating table and place it in water to cool it down. (2) Place the iron column in an auxiliary fixing ring to ensure that the boundaries of the two are in contact and that the iron column does not swing back and forth during the thinning process. Use 7000 mesh sandpaper in the grinder and water as the grinding liquid. Add water at a rate of 20 mL / min and grind for 3 min at a speed of 70 r / min. After sandpaper grinding, polishing is performed with a W2.5 red velvet polishing cloth and polishing is performed with an aluminum oxide polishing liquid with a particle size of 0.5 μm for 10 minutes. The acceleration rate and rotation speed of the grinding liquid droplet are the same as above to remove the scratches caused by sandpaper grinding and further thinning and polishing; (3) The ground and polished YIG film is removed from the iron column, and acetone is used to remove the hot melt adhesive and other impurities and dirt; (4) The cleaned YIG film is argon ion etched to further thin and improve the surface roughness. The etching process parameters are set to a gas flow rate of 8 sccm, an argon ion beam incident angle of 90°, an argon ion energy range of 490 eV, and an ion beam current density of 0.5 mA / cm 2 , beam current 95mA, effective ion beam diameter 150mm, single etching time is 600s.
[0062] Comparative Example 1
[0063] (1) Place a cylindrical iron column with a diameter of 20 mm, a height of 60 mm, and a weight of 180 g on a heating table. After heating, apply a certain amount of hot melt adhesive and place a 3 mm × 3 mm YIG film on it. Then remove it from the heating table and place it in water to cool it down. (2) Place the iron column in an auxiliary ring to ensure that the boundaries of the two are in contact and that the iron column does not swing back and forth during the thinning process. Use 7000 mesh sandpaper in the grinder and water as the grinding liquid. Add water at a rate of 20 mL / min and grind for 3 min at a speed of 70 r / min.
[0064] Comparative Example 2
[0065] (1) The YIG film was cleaned by ultrasound to remove surface impurities and dirt, and then ion etching was performed to thin the film and improve the surface roughness. The etching process parameters were set to a gas flow rate of 8 sccm, an argon ion beam incident angle of 90°, an argon ion energy range of 490 eV, and an ion beam current density of 0.5 mA / cm 2 , beam current 95mA, effective ion beam diameter 150mm, single etching time is 600s.
[0066] Experimental example
[0067] The YIG films prepared in the examples and comparative examples were tested by means of SEM and AFM.
[0068] The SEM and AFM images of the YIG film obtained in Example 1 are shown in Figure 1 and Figure 2 The initial thickness of the YIG film of Example 1 sample is 10.0 μm, and the final film thickness is about 4 μm, for example Figure 1 4.223 μm, 3.794 μm, 4.221 μm, etc. The thinning rate in the mechanical grinding stage and the final film surface roughness RMS in Example 1 are 0.446 μm / min and 1.939 nm respectively.
[0069] The SEM and AFM images of the YIG film obtained in Comparative Example 1 are shown in Figure 3 and Figure 4 The initial thickness of the YIG film of the sample in Comparative Example 1 is 9.0 μm, and the thickness of the final film is significantly greater than the thickness of the film obtained in Example 1. Figure 3 The thickness reduction rate and roughness RMS of the YIG film prepared in Comparative Example 1 are: 0.779 μm / min, 3.422 nm.
[0070] The SEM and AFM images of the YIG film obtained in Comparative Example 2 are shown in Figure 5 and Figure 6 The initial thickness of the YIG film of the sample in Comparative Example 2 is 8.0 μm, and the thickness of the final film is significantly greater than the thickness of the film obtained in Example 1, for example Figure 5 The thickness reduction rate and roughness RMS of the YIG film prepared in Comparative Example 2 are: 0.882 μm / h, 0.496 nm.
[0071] Results and Discussion
[0072] The product of comparative example 1 is compared with the YIG thin film material obtained in example 1. The AFM images of the two are as follows: Figure 4 , Figure 2 As shown in the figure, it can be seen that Example 1 quickly reduces the thickness through mechanical thinning, and then uses ion etching to improve the surface roughness. The YIG film prepared by this method not only has a fast thinning rate, but also has a greatly improved film roughness compared to Comparative Example 1. It can be clearly found from the AFM image that there are huge scratches on the YIG film prepared in Comparative Example 1, and the naked eye can also observe that there are many scratches on the sample after grinding. In addition, its surface roughness is also higher than that of Example 1.
[0073] The product of comparative example 2 is compared with the YIG thin film material obtained in example 1. The SEM images of the two are as follows: Figure 5 , Figure 1As shown in the figure, it can be seen that Example 1 can complete the main part of the YIG film thickness thinning within 3 minutes by using mechanical thinning to quickly reduce the thickness, while the thinning rate of ion etching for only 1 hour is very low. Compared with Example 1, it takes longer to complete the thinning of the same thickness, which is not good for the instrument and energy consumption.
[0074] Although the present invention has been described above in conjunction with the exemplary embodiments and the accompanying drawings, it should be apparent to those skilled in the art that various modifications may be made to the above-described embodiments without departing from the spirit and scope of the claims.
Claims
1. A method for thinning and surface treatment of a YIG film, characterized in that: The method comprises: (1) Use sandpaper to perform major thinning of the YIG film; (2) using a W1.5-W2.5 polishing cloth to thin and polish the YIG film treated in step (1) to remove surface scratches and improve roughness; (3) Using argon ion etching and polishing technology, the YIG film treated in step (2) is thinned and polished.
2. The YIG thin film thickness reduction and surface treatment method according to claim 1, characterized in that: The mesh number of the sandpaper is ≥7000 meshes and ≤10000 meshes.
3. The YIG film thickness reduction and surface treatment method according to claim 1, characterized in that: Step (1) is carried out on a grinder, wherein the rotation speed of the grinder is 60 to 70 r / min, the grinding liquid comprises water, the grinding liquid droplet acceleration rate is 20 to 30 mL / min, the applied pressure is 0.2 to 0.25 MPa, and the grinding time is 3 min ± 10 s.
4. The YIG thin film thickness reduction and surface treatment method according to claim 1, characterized in that: Step (2) is carried out based on a grinder, wherein the grinder speed is 60-70 r / min, the grinding liquid is an aluminum oxide polishing liquid with a particle size of 0.5-2 μm, the grinding liquid droplet acceleration rate is 20-30 mL / min, the applied pressure is 0.2-0.25 MPa, and the polishing time is 10 min ± 10 s.
5. The YIG thin film thickness reduction and surface treatment method according to claim 1, characterized in that: The polishing cloth comprises a red velvet polishing cloth.
6. The YIG thin film thickness reduction and surface treatment method according to claim 1, characterized in that: Prior to step (3), the method further comprises: cleaning the YIG film treated in step (2).
7. The YIG thin film thickness reduction and surface treatment method according to claim 6, characterized in that: Acetone was used for the cleaning.
8. The YIG thin film thickness reduction and surface treatment method according to claim 1, characterized in that: The process parameters of the argon ion etching polishing technology described in step (3) include: gas flow rate of 7-10 sccm, argon ion beam incident angle of 80-90°, argon ion energy range of 100-1000 eV, ion beam current density of 0-1 mA / cm 2 , beam current 0 ~ 130mA, effective ion beam diameter ≥ 100mm, single etching time is 10 ~ 600s.
9. A YIG film with low surface roughness, characterized in that: The YIG film is obtained by the method according to any one of claims 1 to 8, and the roughness of the YIG film with low surface roughness is ≤2nm and the thickness is 1 to 50μm.
10. Use of the YIG film according to claim 9 in microwave devices.
Citation Information
Patent Citations
Preparation method of transmission electron microscopy film sample for in-situ application of electric field and stress
CN104819876A
Ti / Si co-doped ta-C conductive carbon-based thin film and preparation method and application thereof
CN115058696A
Semiconductor material thinning and polishing method and device
CN116936344A
Separate injection of reactive species in selective formation of films
US20090163001A1
Power Combiner and Microwave Introduction Mechanism
US20160358750A1